2010
DOI: 10.1083/jcb.200912082
|View full text |Cite
|
Sign up to set email alerts
|

MAPK signaling to the early secretory pathway revealed by kinase/phosphatase functional screening

Abstract: An RNAi screen determines that the early secretory pathway is subject to phosphoregulation via a variety of signaling pathways, including a link between growth factor signaling and ER export.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
212
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(226 citation statements)
references
References 51 publications
(73 reference statements)
14
212
0
Order By: Relevance
“…For example, signaling by growth factors (e.g. MAPK/ERK) at plasma membranes affects the early secretory pathway (anterograde transport) via the ERES (Farhan et al, 2010). Thus, it is important to investigate the overall balance of membrane trafficking between the relevant organelles, as well as the plasma membrane, to elucidate the changes in Golgi and ER morphology that occur during mitosis more fully.…”
Section: Discussionmentioning
confidence: 99%
“…For example, signaling by growth factors (e.g. MAPK/ERK) at plasma membranes affects the early secretory pathway (anterograde transport) via the ERES (Farhan et al, 2010). Thus, it is important to investigate the overall balance of membrane trafficking between the relevant organelles, as well as the plasma membrane, to elucidate the changes in Golgi and ER morphology that occur during mitosis more fully.…”
Section: Discussionmentioning
confidence: 99%
“…Farhan and colleagues investigated the role of human kinases and phosphatases in the distribution of membrane markers of the early secretory pathway, and showed that growth factor signalling regulates ER export through ERK2. Besides the MAPK signalling pathway, a number of other signalling networks, such as those involving insulin, phosphatidylinositol or toll-like receptor signalling, were also found to have a role in the regulation of the early secretory pathway (Farhan et al, 2010).…”
Section: Stedmentioning
confidence: 99%
“…Such an automated, integrated approach has recently been used to identify, at genome level, those genes that, when knocked down, cause alterations in biosynthetic protein trafficking (Simpson et al, 2012) and organelle integrity (Farhan et al, 2010;Kondylis et al, 2011;Simpson et al, 2012). Farhan and colleagues investigated the role of human kinases and phosphatases in the distribution of membrane markers of the early secretory pathway, and showed that growth factor signalling regulates ER export through ERK2.…”
Section: Stedmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with chemical compounds or specific gene silencing by RNA interference are commonly used at the scale of individual experiments to highthroughput studies. Visual inspection by expert biologists has been performed for several decades, ranging from early studies by microscopists like Ramon y Cajal to contemporary large scale, high-throughput screens (1)(2)(3)(4). Although human observation may be very accurate, the three major drawbacks are that (i) it lacks quantitative measures, (ii) it may be biased, and (iii) it is time consuming.…”
mentioning
confidence: 99%